Conducting a Hispanic health needs assessment in rural Kansas: building the foundation for community action - Bopp, Melissa; Fallon, Elizabeth A.; Bolton, Debra J.; Kaczynski, Andrew T.; Lukwago, Susan; Brooks, Alicia (My University, 2012)
Healthy People 2020 states that ethnic health disparities are a priority for the US. Although considerable national statistics document ethnic-related health disparities, information specific to rural areas is scarce and does not provide direction for implementing chronic disease prevention programming. Therefore, the purpose of our project was to undertake the Hispanic Health Needs Assessment (HHNA), a tool designed by the National Alliance for Hispanic Health (NAHH), in culturally-diverse rural Southwest Kansas. Our focus areas included: access to healthcare, heart disease, diabetes, overweight, nutrition, and physical activity. Methods: The assessment followed six steps: (1) developing the assessment team, (2) data gathering using community member surveys, existing statistics, and community leader interviews, (3) assembling the findings, (4) formulating recommendations for action at individual, institutional, community and policy levels, (5) sharing findings and program planning (6) sharing findings with NAHH. We identified several challenges collecting health related data in rural communities. But overall, the HHNA was a comprehensive and useful tool for guiding a community level health assessment. Conclusion: This process has provided our community partners with locally relevant statistics regarding the current status of health, health behaviors, and perceived community needs to inform resource allocation, program planning and applications for new funding initiatives.
Keywords: Community based; Needs assessment; Hispanic